PENGARUH MODAL KERJA DAN PERPUTARAN PIUTANG TERHADAP PROFITABILITAS PADA PT. PELABUHAN INDONESIA IV (PERSERO) CABANG MAKASSAR - Silvister Saman (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2016)
The purpose of the study was to examine the effect of working capital and accounts receivable turnover to profitability partially or simultaneously on PT. Pelabuhan Indonesia IV (Persero) Branch Makassar. While the analysis used in this research is the analysis of quantitative data processing analysis shaped figure (numeric), and Statistical Analysis multiple linear regression (Multiple). The results of this study are Partial Working Capital owned by PT. Pelabuhan Indonesia IV (Persero) Branch Makassar positive and significant impact on profitability that is equal to 0.581. Partial Accounts Receivable Turnover owned PT.Pelabuhan Indonesia IV (Persero) Branch Makassa positive and significant impact on profitability is equal to 948. Simultaneous Working Capital and Receivables Turnover at PT. Pelabuhan Indonesia IV (Persero) Branch Makassar no significant effect on the profitability of F smaller than F table (0.224 <19.00),